Social Systems of Flexible Production: Organizational Conditions for the Resurgence of Craft - Nyfeler Judith (Journal of Organizational Sociology)
Against the background of a growing interest in the resurgence of craft work, this article examines the organizational conditions that characterize craft-based production in contemporary society and how they help to facilitate craft resurgence. The paper identifies three organizational conditions of contemporary craft-based production, relating to the mass market, producing by means of flexible specialization, and using infrastructures. By applying a historical lens, I argue that these organizational conditions have formed into a particular way of organizing craft-based production which is attuned to local and temporal specificities. Therefore, this study builds on a complementary, symbiotic notion of craft which considers industrial manufacture, serial production and digital technologies to be constitutive of craft making. By offering an alternative conceptual framework to grasp the resurgence of craft, this article contributes to the understanding of organizational resilience.